Exploring Impact Factors on Earnings Management Practices - Suwandi, Suwandi; Lambyombar, Yustinus; Junaidi, Muhammad; Yuliana, Yuliana (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Earnings act as a measure of a company's performance and are frequently associated with tactics related to managing earnings. This causal study seeks to investigate how deferred tax expenses, tax planning, and firm size affect earnings management practices. The study sample encompasses 13 food and beverage industries in the Indonesian capital market from 2018 to 2022. The sample was selected using a purposive sampling approach. The data for this study is in the form of published financial reports of sample companies, which were collected using the documentation method. Our analytical approach in this investigation was multiple linear regression. The findings show that tax planning and firm size have a significant positive impact on earnings management practices. However, deferred tax expenses show a non-significant negative influence on such practices. In this regard, the implementation of the internal control system needs to be improved to mitigate potential financial manipulation.